A reverse form of welfarism: some reflections on Australian housing policy. Issue 1 (April 2015) - Jacobs, Keith
Abstract : In this paper I argue that we have been amiss in diagnosing the role played by government, which has exacerbated the housing problems afflicting low‐income households in Australia. However, I argue further we have placed too much faith in the capacity of managerial interventions to ameliorate what are far more deep‐rooted and systemic challenges. It is suggested that researchers need to adopt a more critical account of the conduct of contemporary government policy making, one that casts aside a view of the State as a benevolent agency whose primary objective is to ameliorate the conditions of the disadvantaged. Instead, the State should be understood as an agency that sustains the conditions necessary for the finance industry, developers and real estate agents, along with well‐off householders and landlords, to reap profits. The political economy of Australian housing, in its current incarnation, performs a form of reverse welfarism that exacerbates social inequality.